(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Phraseological units of Western Polissya, which characterize original appearance of «woman» and «man», are analysed in the article, in particular hairs. The general and distinctive features of women and men are traced in areal space of the explored region, that means the phraseosemantic row of «Hairs».